THE SUCCESSFUL TREATMENT OF A PERIPHERAL VENO-VENOUS EXTRACORPOREAL MEMBRANE OXYGENATION FOR SEVERE ACUTE RESPIRATORY FAILURE IN THE EARLY PERIOD AFTER ADULT LIVER TRANSPLANTATION - V. N. Poptsov; Y. G. Moysyuk; E. A. Spirina; M. N. Kornilov; L. Y. Moysyuk (Вестник трансплантологии и искусственных органов)
Aim: of our clinical study was to present own experience of veno-venous extracorporeal membrane oxygenation (VV ECMO) for the treatment of an adult patient (female, 28 yrs, 150 cm, 35 kg) with acute respiratory distress syndrome (ARDS) in the early period after liver transplantation against satisfactory liver graft function. Materials and methods. Double-lumen cannula 22 F was placed percutaneously in the right internal jugular vein. The ext- racorporeal contour reduced in length and the polymethylpeptene oxygenator (priming volume 175 ml) were also. Results. In 1 hour after the beginning of VV ECMO, we registered the noted improvement of arterial blood gas and acid-base balance (regress of respiratory acidosis, improvement of arterial oxygenation) which allowed us to use the «protective» mode of mechanical ventilation. Improvement of gas exchange and regress of clinical and radiological manifestations of ARDS allowed for VV ECMO weaning and decannulation on day 7. The patient was discharged from ICU and then from our Centre to a homestay respectively on the 9th and 16th day after VV ECMO weaning with the satisfactory liver graft and lungs function. Conclusion. VV ECMO can be successfully applied to correct the life-threatening acute respiratory failure in the early period after liver transplantation.